Understanding Sex Offender Community Supervision: A Mixed Methods Approach - Schaefer, Roger L. (International journal of offender therapy and comparative criminology, 2019)
The process of transitioning from prison to the community poses unique challenges for those who have been convicted of sexually based offenses. Due to the realities associated with the unique challenges facing these individuals, the community supervision process fluctuates along the correctional continuum which polarizes rehabilitative and control. The current study examines how this fluctuation relates to both the supervision process and correctional outcomes. Furthermore, the literature suggests five specific checkpoints along this continuum which are measured both qualitatively and quantitatively. The five checkpoints are Social Reintegration, Community Reentry, Status Maintenance, Statutory Compliance, and Risk Management. Overall, all five checkpoints are included in some way in the community supervision process; and analyses show significant links between the checkpoints and correctional outcomes.